Regarding the standardization of L-arginine and thiotriazoline in the model mixture by high-performance liquid chromatography - L. I. Kucherenko; O. V. Khromylova; D. Yu. Skoryna; H. I. Tkachenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Today, one of the main causes of disability and mortality in the world's population is the disease of the cardiovascular and central nervous systems. Therefore, the development of new highly effective drugs for their treatment becomes an urgent task of modern medicine and pharmacy. Promising in this direction is the creation of a new medicinal product, which combines the active donor NO – neurotransmitter amino acid L-arginine, as well as the famous domestic antioxidant – thiotriazoline. A rational dosage form – pills was chosen to create a new combined drug. Therefore, the actual and timely task is to develop methods for standardizing the active substances in the model mixture, which in future can become the basis for the analysis of the finished dosage forms of the new drug.